2007
DOI: 10.3151/jact.5.333
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation Reaction of Calcium Silicate Hydrates by Hydrothermal Synthesis at 150°C in OPC-γ-Ca<sub>2</sub>SiO<sub>4</sub>-α-Quartz Systems

Abstract: In order to develop organic-fiber reinforced building materials with long-term stability and durability, the carbonation of autoclaved calcium silicate hydrate hardening bodies, prepared by low-temperature synthesis (150°C) in Ordinary Portland Cement (OPC)-γ-Ca 2 SiO 4 (γ-C 2 S)-α-quartz systems, has been investigated. The CO 2 absorption decreased remarkably as the water-to-powder ratio (w/p) of the samples decreased, and the carbonation of the samples was inhibited. In addition, this tendency became remarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…e gaps between porosity of noncarbonated and carbonated samples were more obvious as the replacement ratio increases. Vaterite formed by the carbonation of c-C 2 S is denser than calcite and aragonite (vaterite: 2.645 g/cm 3 , calcite: 2.711 g/cm 3 , and aragonite: 2.944 g/cm 3 ) [42].…”
Section: Tga Analysismentioning
confidence: 96%
“…e gaps between porosity of noncarbonated and carbonated samples were more obvious as the replacement ratio increases. Vaterite formed by the carbonation of c-C 2 S is denser than calcite and aragonite (vaterite: 2.645 g/cm 3 , calcite: 2.711 g/cm 3 , and aragonite: 2.944 g/cm 3 ) [42].…”
Section: Tga Analysismentioning
confidence: 96%
“…5) Moreover, Saito further reported that, the residual γ -C2S after autoclave curing reacts with CO2 during accelerated carbonation curing in OPC-γ -C2S-α -Quartz systems. 6) This material design for high durability of cementitious materials containing γ -C2S presented by Saito 6) and Yumoto 7) is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…The autoclave curing process formulated the generation of large amount of 1.1nm tobermorite in the hardened cement matrix. 8) And then, accelerated carbonation curing formed the vaterite at the surface of specimen leading to the surface densification. The densification of the surface prevented the penetration of chloride ions.…”
Section: Introductionmentioning
confidence: 99%